Dialects, motivation, and English proficiency: Empirical evidence from China - Marjerison, Rob Kim; Yang, Shuo (Frontiers in Psychology, 2022)
Within the context of China, this study seeks to examine the relationship between English language proficiency, the native dialect of the learner, and the learner's reason, or motivation for learning English. English language proficiency can be an important vehicle for accessing high-quality higher education and for enhancing employment and career opportunities, both of which are important tools in poverty reduction, encouraging economic development, and as tools for socioeconomic mobility. Data was gathered through an online survey with 985 usable responses recorded. Respondents included a distribution of speakers from five of the major distinct dialects of China. The analysis provides empirical evidence of a diversity of propensities and motivations for English language acquisition among learners from different regions and native dialects. The results of this study may be of interest to policymakers, linguists, educators, and those with an interest in socioeconomic sustainability through language acquisition and education as a method of poverty reduction.